Diferenciación alimentaria entre los sexos de Glossophaga soricina (Chiroptera: Phyllostomidae) en México - Alvarez, Tícul (1999)
To study alimentary differences of !be bat Glossophaga soricina in Mexico, individual and sexual variation were recorded in 238 stomach contents from several localities aud dates. Samples were c1assified in nine groups to avoid seasonal and geographical bias. Individual differences (studied only in females) identified one dominant plant species by locality, but with exceptions, suggesting individual opportunistic or feeding preferences. For sexual differences a "Gw" test (with William's correction) was applied; f our bat groups have important differences, four groups have minor differences and in one group, male and female diets were similar.